Avaliação do potencial de uso agrícola da fluorita com óxido silício (AgroSiCa), derivado da fabricação de fertilizantes fosfatados - Valle, Lucas Alberth Ribeiro (2016)
Phosphate fertilizers are critical for crop production in tropical soils, which are known for having high phosphate-fixing capacity and aluminium saturation, as well as low pH and calcium contents. Fluorine is a component of many phosphate rocks used to make phosphate fertilizers, via a process that generates hexafluorosilicic acid (H2SiF6). While many treatment technologies have been proposed for removal of fluorine in industrial facilities, little attention has been given to a process of neutralizing H2SiF6 with calcium oxide aiming to find out an alternative and sustainable use of a by-product with a great potential for beneficial use in tropical agriculture. This study evaluated the effect of a by-product of phosphoric acid production (fluorite with silicon oxide, hereafter called AgroSiCa) in levels of phosphorus (P), calcium (Ca), silicon (Si), aluminum (Al) and fluorine (F) and some others parameters in soils as on growth of soybean and corn. Experiments were conducted in a greenhouse condition at the Federal University of Lavras (UFLA), Lavras, Minas Gerais, using different types of soils in tropical regions and different doses of AgroSiCa. The application of AgroSiCa resulted in a slight increase in soil pH and significant increases in calcium, phosphorus and silicon in the soil solution and the shoots of corn and soybeans. We also found very low levels of fluoride in all soil leachates. A significant reduction of labile aluminum levels found in all soils after the cultivation of corn and soybeans. In sum, AgroSiCa improved soil properties and contributed to better growth of both cultures. In sum, AgroSiCa improved soil properties and contributed to a better growth of both crops. Our results show that reacting H2SiF6 derived from the wet-process phosphoric acid production with calcium oxide leads to a by-product with potential for agricultural use, especially when applied in highly-weathered soils. Besides providing calcium and silicon to plants, the use of such by-product in soils with high phosphate-fixing capacity and high aluminium saturation delivers additional benefits, since fluoride and silicon can play an important role in improving soil conditions due to the formation of less plant-toxic forms of aluminium, as well as upon decreasing phosphate fixation, thus improving root development and making fertilizer-derived phosphate more available for plant growth.